International sourcing, domestic labour costs and producer prices - Sotiris Blanas; Maurizio Zanardi (National Bank of Belgium, 2024)
Using a representative sample of firms in Belgian manufacturing over 2001Q1-2017Q4, we study the effects of their international sourcing activities and domestic wages on their domestic output prices, as well as the effects of international sourcing on (relative) domestic wages. Controlling for firm size and other factors, we find that higher shares of imported intermediates, especially when they originate from lower-income countries, result in lower domestic output prices. This is consistent with the costsaving aspect of international sourcing. For high-tech products, however, we also find that higher shares of imported intermediates from high-or lower-income countries lead to higher domestic prices. This is consistent with the input quality-enhancing aspect of international sourcing, but also its costsaving aspect allowing for the re-allocation of domestic resources towards innovation and technologyintensive activities. In addition, we find that the share of imported intermediates from high-income countries is differentially negatively associated with the wage bill share and relative wage for whitecollar workers in high-tech firms. Taken together, we view these results as suggestive evidence of firms combining higher-quality foreign inputs and domestic labour-especially blue-collar workers- in order to service the domestic market with higher-quality outputs at higher prices.
Keywords: F10; F14; E31; 330; International sourcing; importing; intermediates; wages; producer prices